FIRST RECORD OF Costalimaita ferruginea (FABRICIUS, 1801) (COLEOPTERA: CHRYSOMELIDAE) IN EUCALYPTUS IN MATO GROSSO DO SUL STATE - Kassab, Samir Oliveira (2011)
The occurrence of the eucalyptus yellow beetle Costalimaita ferruginea (Fabricius, 1801) (Coleoptera: Chrysomelidae) was repoted in November 2009 in clonal plantations of Eucalyptus grandis x Eucalyptus urophylla in Três Lagoas, Mato Grosso do Sul state. This is the first record of this species of eucalyptus seedlings in this state. In Brazil, Costalimaita ferruginea is considered a major pest of eucalyptus because of its ability to cause injuries such as the apical defoliation in parts of the plant, promoting significant losses in the development and inhibiting the marketing of wood and its derivatives.